Digital Information System for Mapping Health Crisis Response Capacity in Bali Province - Cetiawan, Arie; Sudipa, I Gede Iwan (PT.KARYA GEMAH RIPAH, 2025)
The Bali Provincial Health Office is currently mapping disaster locations and health facility capacities in and around affected areas using analog maps. However, these maps have several limitations that slow down officers in preparing the necessary information required by leadership for decision-making in health crisis management. Therefore, a digital mapping system is urgently needed to facilitate and accelerate the compilation of information, enabling quick and efficient decision-making. This study employed data collection methods through interviews and visual observations. The outcome is a capacity mapping information system that supports the Health Office in managing disaster and health crisis responses by integrating disaster maps and health service capacities. System testing was conducted 32 times using the Black Box Testing method, with standards based on predefined testing scenarios.